The Kampala Convention as an example of regionalization of international law: prerequisites for adoption and general characteristics - Hrekul-Kovalyk, T. A. (Науковий вісник Ужгородського національного університету. Серія Право, 2025)
The study is devoted to the analysis of the process of regionalization of international law on the African continent through the prism of formation and development of the legal mechanism for protection of the rights of internally displaced persons. The relevance of the topic is due to the dynamic growth of internal displacement in Africa caused by armed conflicts, ethnic confrontations, political instability and natural disasters. The author finds that the Organization of African Unity first paid attention to the problem of population displacement in the region in 1969, when the Convention relating to the Status of Refugees was adopted, which launched the African «open door policy». However, since the late 1970s, the nature of the problem has undergone a significant transformation: there is a need for regional legal solutions to protect internally displaced persons. The article examines the historical, political and legal prerequisites for the adoption of the Kampala Convention, the first binding regional treaty specifically designed to protect the rights of internally displaced persons. The author traces the stages of development of the regulatory framework: from seminars and declarations of the OAU and AU to the conclusion of the Great Lakes Pact and the relevant protocols that laid the foundation for the future Convention. The author defines the role of the African Union in initiating the process of concluding the Kampala Convention and emphasizes key aspects of its content, including the prioritization of state responsibility, the prevention of arbitrary displacement, the protection of vulnerable groups, and the assurance of voluntary return for displaced persons. The Kampala Convention is seen as an innovative mechanism due to its comprehensive and binding nature, as well as an example of the implementation of the principle of «African solutions for African problems». It is established that despite significant progress in the legal regulation of internal displacement, a number of States have not yet ratified the Convention. All of this highlights the need for further analysis of the causes of institutional inertia and the identification of effective tools for implementing its provisions within the national legal systems of African countries.